«Historical Narratives and society in Peru» Current analytical constructs about National Reality - Castillo Ochoa, Manuel (2021)
Since the second decade of XXI century in the Peruvian society the political situation has been polarized. Narratives emerged in this context and try to justify their political activity. The essay seeks to show specially, these narratives recognized as historic. It also pretends to show its origin, arguments, and proposals. Moreover, from the «hermeneutic perspective», it intends to investigate about the importance that they acquire as a main semantic component in current societies. As well as their relation to the interpretive and discursive theoretical tendencies.